Analisis Pengaruh Tingkat Pengagguran Terbuka Jumlah Penduduk dan Pendidikan terhadap Tingkat Kemiskinan Provinsi Jawa Tengah - Urwatut Diyanah; Syamsul Huda (CV. Ulil Albab Corp, 2022)
Equitable development is an effort that is always maximized by every developing country, but the existence of poverty is a definite problem and always owned by every country. The purpose of this study was to determine the effect of the open unemployment rate, population and education on the poverty rate in Central Java province in 2006-2020. The data in this study used secondary data obtained from the Central Statistics Agency of Central Java in the form of time series data. This study used quantitative methods processed by multiple linear analysis with the Ordinary Least Square (OLS) model using SPSS 23.0 for windows. The results of this study show that simultaneously the variables of open unemployment rate, population and education affect the poverty rate in central Java province. And partially the open unemployment rate has a positive and significant effect on the poverty rate in Central Java, the number of people negatively affects the poverty rate in Central Java, education does not affect the poverty rate in Central Java.